Gendered Language and Patriarchal Control in Jamaica Kincaid’s Girl (1978): A Feminist Discourse Analysis - Bella Renata Br. Manalu; Roselyn Gracia Sitompul; Katarina Aureli Fiona; Enjelina Rointan Ambarita; Vivi Novika Sitinjak (Pustaka Digital Indonesia, 2026)
The urgency of this study lies in its critical examination of how gendered language functions as a tool of patriarchal control in Jamaica Kincaid’s Girl (1978), revealing how linguistic practices shape female identity, social expectations, and power relations within a cultural context. This study examines gendered language in Jamaica Kincaid’s short story Girl (1978) by focusing on how linguistic forms function as mechanisms of social control over women. Rather than treating gendered language as a general phenomenon, this research specifically analyzes the dominance of imperative sentences, repetition, and normative diction used by the mother figure to construct female identity within a patriarchal cultural framework. Using a qualitative descriptive method and feminist discourse analysis, the study identifies how directives and prohibitions directed at the female subject reflect expectations of obedience, domestic responsibility, and moral discipline. The findings reveal that language in Girl does not merely mirror gender norms but actively reproduces them by normalizing patriarchal values through everyday maternal discourse. The study concludes that Kincaid’s Girl demonstrates how language operates as an ideological tool that shapes and limits women’s identities, highlighting the importance of feminist linguistic analysis in literary studies.